Functional health literacy and adherence to the medication in older adults: integrative review - Martins,Nidia Farias Fernandes (2017)
ABSTRACT Objective: to characterize the national and international scientific production on the relationship of Functional Health Literacy and the adherence to the medication in older adults. Method: integrative review of literature, searching the following online databases: Scientific Electronic Library Online (SCIELO); Latin American and Caribbean Health Sciences Literature (LILACS); Medical Literature Analysis and Retrieval System Online (MEDLINE); and Cumulative Index to Nursing & Allied Health Literature (CINAHL), in June 2016. We selected 7 articles that obeyed the inclusion criteria. Results: all articles are from the USA. The inappropriate Functional Health Literacy affects the non-adherence to medication; however, there are several strategies and interventions that can be practiced to change this relationship. Conclusion: nursing needs to explorefurther this theme, since it can exert a differentiated care for adherence to medication in older adults, considering the literacy.